Scrub typhus: a hospital-based study in the northern districts of West Bengal, India - Mallick, Sanjay Kumar; Hazra, Santanu; Nandi, Tanmoy; Sarkar, Arunabha (International Journal of Research in Medical Sciences, 2019)
Background: Scrub typhus caused by Orientia tsutsugamushi, is a mite-borne zoonotic acute febrile illness. Geographically, it is confined to the Asia-Pacific region and important re-emerging infection in India. Clinical diagnosis of scrub typhus from other acute febrile illness is very difficult due to nonspecific symptoms and the relative absence of eschar in the Indian population. Case fatality rate varies from 30-70% depending on the clinical suspicion, delay in diagnosis and treatment. Antibody-based serological tests are the mainstay of diagnosis. IgM enzyme-linked immunosorbent assay (ELISA) against O. tsutsugamushi is helpful for the diagnosis of scrub typhus within the first week of illness. Methods: The aim of the study was to determine the prevalence of the disease in Northern districts of West Bengal, India using IgM ELISA. Results: Out of 577 serum samples tested 10.05% were positive for IgM antibodies. Majority of cases were below 40 years of age with higher prevalence in female patients. The disease showed a seasonal trend with a peak during the monsoon and later months. The case fatality rate among ELISA positive cases was 32.76%. Conclusions: Significant seropositivity against scrub typhus among cases of acute febrile illness with relatively higher mortality indicates that scrub typhus should be included in the differential diagnosis and confirmed by IgM ELISA.